Disease Risk and Conservation Implications of Orangutan Translocations - Sherman, Julie; Unwin, Steve; Travis, Dominic A.; Oram, Felicity; Wich, Serge A.; Jaya, Ricko L.; Voigt, Maria; Santika, Truly; Massingham, Emily; Seaman, Dave J. I.; Meijaard, Erik; Ancrenaz, Marc (Frontiers in Veterinary Science, 2021)
Critically Endangered orangutans are translocated in several situations: reintroduced into historic range where no wild populations exist, released to reinforce existing wild populations, and wild-to-wild translocated to remove individuals from potentially risky situations. Translocated orangutans exposed to human diseases, including Coronavirus Disease 2019 (COVID-19), pose risks to wild and previously released conspecifics. Wildlife disease risk experts recommended halting great ape translocations during the COVID-19 pandemic to minimize risk of disease transmission to wild populations. We collected data on orangutan releases and associated disease risk management in Indonesia during the COVID-19 pandemic, and developed a problem description for orangutan disease and conservation risks. We identified that at least 15 rehabilitated ex-captive and 27 wild captured orangutans were released during the study period. Identified disease risks included several wild-to-wild translocated orangutans in direct contact or proximity to humans without protective equipment, and formerly captive rehabilitated orangutans that have had long periods of contact and potential exposure to human diseases. While translocation practitioners typically employ mitigation measures to decrease disease transmission likelihood, these measures cannot eliminate all risk, and are not consistently practiced. COVID-19 and other diseases of human origin can be transmitted to orangutans, which could have catastrophic impacts on orangutans, other susceptible fauna, and humans should disease transmission occur. We recommend stakeholders conduct a Disease Risk Analysis for orangutan translocation, and improve pathogen surveillance and mitigation measures to decrease the likelihood of potential outbreaks. We also suggest refocusing conservation efforts on alternatives to wild-to-wild translocation including mitigating human-orangutan interactions, and enforcing laws protecting orangutan habitats in agricultural concessions to conserve orangutans in situ.